Discoursive digital genres: Fanfiction and twitterature (Contextos: Estudios de Humanidades y Ciencias Sociales, 2019)
Human communication is carried out through different discursive forms that are created or develop over time. Communication was digitalized a new discursive genre appear or adapt to the technological environment to fulfill different functions that users require. Although these are transformations of discourses that already existed in the pre-digital era, it is pertinent to reflect on these genres in order to highlight their characteristics, specifically fanfiction and Twitterature.